Benefits of probiotics in Autism Spectrum Disorders : A meta-analysis of RCTs - Sharanabasayyaswamy B. Hiremath; Srinivas L. Devendrappa (Pharmacology and Clinical Pharmacy Research, 2023)
Using probiotics as a pharmaceutical intervention is based on the fact that dysbiosis affects many people with autism spectrum disorders (ASD). This study aimed to quantify various probiotics’ overall and individualized benefits in treating ASD. Randomized or cross-over trials comparing the efficacy of placebo or active control vs. probiotics in patients of any age diagnosed with ASD based on DSM IV/V criteria were considered under inclusion criteria.  An electronic database search in PUBMED and Cochrane Library was conducted using MeSH search terms “probiotics” AND “Autism.”  Mean change in the total score of clinical parameters used to assess ASD symptom severity was the primary outcome measure analyzed. All the outcome measures were estimated by calculating the Standardized Mean Difference (SMD) values and their 95% Confidence Intervals (CI), considering the different clinical parameters used to assess the change in ASD symptoms in identified clinical trials. An insignificant decrease in the total score value of primary outcome measure by -0.14 (SMD: 0.14, 95% CI:-0.45 to 0.17) in patients treated with probiotics was observed. The quantity of decrease remained insignificant in subgroup analyses also. Observed insignificant clinical benefits of probiotics in ASD patients could be due to the presence of gastrointestinal symptoms as co-morbidity. We hypothesize that intolerance to dietary components is responsible for gastrointestinal symptoms and inflammation. Perhaps probiotics are still beneficial in ASD patients without gastrointestinal symptoms, while their combination with prebiotics is effective in patients with gastrointestinal symptoms.